Implementation of Body Temperature Checking System with Automatic Door Lock Web and Arduino Assistance - Apip Supriana; Bayu Adhi Prakosa; Ritzkal Ritzkal (Jurnal Mantik, 2021)
The main objective of this research is to investigate the implementation of the IOT prototype that contributes to the movement to prevent COVID-19 transmission to support COVID-19 free programs among higher education institutions in Bogor with the implementation of the existing system. Several efforts were made, one of which was checking the body temperature when entering the room. for normal temperature will be allowed to enter and if fever is not allowed to enter. Body temperature measurement can also be done with conventional infrared thermometers that have been circulating in the community, but this infrared thermometer requires guards for its operation who will be at risk of contracting COVID-19. Then a body temperature measurement tool was built using the Arduino Mega2560 microcontroller and web assistance to minimize the spread of COVID-19 when entering the room. There are several methods including Analysis, Design, Implementation, Testing. This tool is designed to use the MLX90614-DCI sensor as a temperature sensor which will be displayed on the LCD if the temperature is normal then the relay will cut off electricity on the electromagnetic door so that the door lock will open and vice versa. The temperature that is read will be stored in the database and will appear on the web to monitor the temperature read by the body temperature measuring device. This tool has been tested for comparison with conventional infrared thermometers with a difference of 0.3oC so that it is feasible to use.